GENDER AND AIDS: EXPLORING AN INTIMATE RELATIONSHIP - Mannell, Jeneviève (PINS-Psychology in Society, 2025)
Hunter, Mark (2010) Love in the time of AIDS. Scottsville, Pietermartizburg: University of KwaZulu-Natal Press. ISBN 978 1 96914 203 2 pbk. Pages 303. Love in the Time of AIDS explores notions of love and intimacy among South Africans as a means of shedding some light on the overwhelming rise in HIV prevalence in some areas of the country from one to 30 percent in only 15 years. Drawing the reader through the history of South Africa’s political economy from colonialism to the post-apartheid and capitalist era, the book provides a compelling account of the ways in which economic forces have interacted with individual ideas about love and sex to produce what Hunter refers to as the “materiality of everyday sex” – where love and relationships are intimately linked with sex for material benefits.